Microchimerism in multiple sclerosis: The association between sex of offspring and MRI features in women with multiple sclerosis - Bianchi, Alessia; Aprile, Maria; Schirò, Giuseppe; Gasparro, Claudia; Iacono, Salvatore; Andolina, Michele; Marrale, Maurizio; Gattuso, Irene; La Tona, Giuseppe; Midiri, Massimo; Gagliardo, Cesare; Salemi, Giuseppe; et al. (Frontiers in Neuroscience, 2023)
Aims. During pregnancy, fetal cells can migrate to the mother via blood circulation. A percentage of these cells survive in maternal tissues for decades generating a population of fetal microchimeric cells (fMCs), whose biological role is unclear. The aim of this study was to investigate the association between the sex of offspring, an indirect marker of fMCs, and magnetic resonance imaging (MRI) features in women with multiple sclerosis (MS). Methods. We recruited 26 nulliparous MS patients (NPp), 20 patients with at least one male son (XYp), and 8 patients with only daughters (XXp). Each patient underwent brain MR scan to acquire 3D-T2w FLAIR FatSat and 3D-T1w FSPGR/TFE. Lesion Segmentation Tool and FreeSurfer were used to obtain quantitative data from MRI. Additional data were collected using medical records. Multiple regression models were applied to evaluate the association between sex of offspring and MS data. Results. Comparing NPp and XXp, we found that NPp had larger 4th ventricle volume (2.02 ± 0.59 vs 1.70 ± 0.41; p=0.022), smaller left enthorinal volume (0.55 ± 0.17 vs 0.68 ± 0.25; p=0.028), and lower thickness in the following cortical areas: left paracentral (2.34 ± 0.16 vs 2.39 ± 0.17; p=0.043), left precuneus (2.27 ± 0.11 vs 2.34 ± 0.16; p=0.046), right lateral occipital (2.14 ± 0.11 vs 2.25 ± 0.08; p=0.006). NPp also had lower thickness in left paracentral cortex (2.34 ± 0.16 vs 2.46 ± 0.17; p=0.004), left precalcarine cortex (1.64 ± 0.14 vs 1.72 ± 0.12; p=0.041), and right paracentral cortex (2.34 ± 0.17 vs 2.42 ± 0.14; p=0.015) when compared to XYp. Comparing XYp and XXp, we found that XYp had higher thickness in left cuneus (1.80 ± 0.14 vs 1.93 ± 0.10; p=0.042) and left pericalcarine areas (1.59 ± 0.19 vs 1.72 ± 0.12; p=0.032) and lower thickness in right lateral occipital cortex (2.25 ± 0.08 vs 2.18 ± 0.13; p=0.027). Discussion. Our findings suggested an association between the sex of offspring and brain atrophy. Considering the sex of offspring as an indirect marker of fMCs, we speculated that fMCs could accumulate in different brain areas modulating MS neuropathological processes.